Periodontal Tissue Health between Adolescents Wearing and Not Wearing Fixed Orthodontic Appliances 15-17 Years Old in Jakarta High School - Sekar Decita; Chaerita Maulani; Helwiyah Umniyati (Lembaga Penelitian Universitas YARSI, 2024)
Abstract Introduction: Treatment of dental malocclusion with fixed orthodontic appliances can lead to plaque collection which can cause periodontal disease. Fixed orthodontic appliances are widely used among adolescents aged 15-17 years in Jakarta high schools because the prevalence of malocclusion in Indonesia is quite high at 80%. Objective: To determine the relationship between the use of fixed orthodontic appliances and periodontal tissue health between adolescents who wear and adolescents who do not wear fixed orthodontic appliances aged 15-17 years in Jakarta High School. Material and Methods: This type of research is comparative analytic with cross sectional research design. Data were collected by clinical examination using the CPITN Index and Gingival Index and filling out an oral hygiene questionnaire. Results: The results of the study on 103 subjects were divided into 50 people who wore fixed orthodontic devices and 53 people who did not wear fixed orthodontic devices. The prevalence of gingivitis based on the Gingival Index of all subjects was 96.11%. The CPITN Index examination resulted in 92.23% having periodontal tissue disease. Chi-Square test of the relationship between subjects who wear and do not wear fixed orthodontic devices with the CPITN Index has a significant relationship P-value = 0.002. Discussion: There is a significant difference between the respondent groups with the CPITN index in accordance with the research of Moosa (2015) and between gender and attitude in accordance with the theory of Lewin (1970) and Green (1991). Conclusion: Subjects who wear and do not wear fixed orthodontic devices have unhealthy periodontal tissue, so subjects must be given counseling and periodontal care.